A Thermodynamic Study of Arsenic Adsorption onto Iron Species Generated by Electrocoagulation - Jose R. Parga; Alhondra de los Santos; Jesús L. Valenzuela (The Minerals, Metals and Materials Society, 2008)
"The present study evaluated the feasibility of using iron species generated by electrocoagulation (EC) as an adsorbent for removal As(III/As(V) from aqueous media. The full potential of EC was evident in that more than 99 percent of arsenic was removed without addition of chemical reagents. The adsorbent iron-species generated by EC was characterized by Chemical Analyses, X-Ray Diffraction and Scanning Electron Microscopy. The experimental data were correlated by employing a Langmuir adsorption isotherm. Thermodynamic parameters such as ?H o , ?S o and ?Go were calculated. The adsorption process was found to be exothermic and spontaneous.1. IntroductionArsenic contamination in potable water supplies is a serious health problem in many countries around the world. Groundwater arsenic contamination in La Comarca Lagunera Mexico was first reported 30 years ago [1]. Arsenic concentration has been found in well water from several communities ranging from 0.25 to 1.0 ppm. The elevated concentration of arsenic in water, above that originating from natural sources, has been attributed to the use of organoarsenical pesticides in the cotton fields and also to the millions of tons of waste slag generated at a local lead smelter [1]. The main arsenic species present in natural waters are arsenate ions 3- 4 AsO (oxidation state V) and arsenic ions H3AsO3, - 2 3 H AsO and 2- 3 HAsO oxidation state III). However, As(V) ions are most prevalent in oxygenated water while As(III) is found for anaerobic conditions, such as in well water or in groundwater. Conventional methods of arsenic removal rely on chemical-based treatment with lime, alum coagulation, iron coagulation and chemical oxidation. Other processes used with varying degrees of success include adsorption onto activated carbon, reverse osmosis, nanofiltration, manganese dioxide, magnetite and ionexchange resins [1-3]. These conventional processes generate a considerable quantity of secondary hazardous waste such as solid sludge, which also pose serious environmental problems. These drawbacks have forced various industries to search for effective, alternative treatment technologies for arsenic with a preference for electrochemical methods."